Impact of Protein Concentration on Polymer and Aggregates Formation During Pasteurisation of Plasma-Derived Human Albumin. - Nadaf, Zakir; Singh, Mohan; Viswanathan, Chandra; Mane, Rahul; Joshi, Sumukh; Sahoo, Sambit Kumar; Ali, Ahamad Fashiu (Plasmatology, 2025)
Background: Human plasma-derived albumin (HA) is a critical therapeutic protein widely used in clinical applications. However, albumin aggregation remains one of the biggest challenges for plasma protein manufacturers worldwide, as it can compromise product stability, efficacy, safety, and yield. Factors that contribute to aggregation include protein concentration, ionic strength, temperature, agitation, pH fluctuations, and stabilizer concentrations during processing. This study examines how varying albumin concentrations affect aggregation under controlled pasteurisation conditions using identical parameters for complete process including agitation, temperature, and stabilizer concentration. Methods: Albumin was purified from human plasma using a modified Cohn's fractionation method, yielding Fraction V intermediate paste. This paste underwent a series of ultrafiltration steps followed by pasteurisation at 60 ± 1 °C for 10 hours, a vital virus inactivation process. To maintain consistency, all influencing parameters such as agitation, temperature, and stabilizer concentrations were kept constant. Three experimental designs were employed: (i) analysing polymer and aggregate formation across multiple batches with albumin concentrations between 20% and 28% having similar starting material i.e. Fraction V paste at 1 kg scale, obtained from manufacturing facility from same manufacturing pool of plasma, (ii) assessing the impact of NaCl at different albumin concentrations during pasteurisation, purified from same lot of Fraction V paste at 1 kg scale, and (iii) performing a trend analysis of polymer aggregate percentage on controlled albumin concentrations (about 25%, 23%, and 21%) in a single batch started at 3 kg scale of Fraction V paste where it was divided into three parts and diluted at three different above mentioned concentrations followed by pasteurisation. Aggregation levels were quantified post-pasteurisation. Results: The findings indicate that albumin concentrations below 23% resulted in significantly higher polymer and aggregate formation (>6.5%), whereas concentrations above 25% reduced aggregation to <. The presence of NaCl had minimal stabilizing effects, particularly at lower albumin concentrations. The trend analysis further confirmed that higher albumin concentrations mitigate heat-induced aggregation, likely due to molecular crowding effects. Conclusion: Albumin concentration plays a crucial role in maintaining structural integrity during pasteurisation, with higher concentrations (>25%) providing enhanced stability. While NaCl contributes to stabilization, it is insufficient at lower albumin concentrations.